Empowering Posyandu Cadres For Pneumonia Prevention: Smoking Exposure And Oximeter Training - Harahap, Huntari; Hanina; Enis, Rina Nofri; aurora, Wahyu Indah Dewi; Asty, Zahra Frizki (LPPM Universitas Jambi, 2025)
Background: Pneumonia remains a major cause of morbidity among toddlers in Indonesia, with household exposure to cigarette smoke acting as a significant and preventable risk factor. Posyandu cadres play a crucial role in community-based child health services; however, their capacity to screen environmental risks and perform early detection of respiratory compromise is often limited. Center, Simpang Kawat Community Health Center, and Paal X Community Health Center in 2024. This community service program aimed to strengthen the knowledge and practical skills of Posyandu cadres in pneumonia prevention through smoking exposure screening and pulse oximeter training Method: A community-based intervention with a pre-test and post-test design was conducted among 20 Posyandu cadres in the working area of the Olak Kemang Community Health Centre, Jambi City. The intervention consisted of interactive health education on secondhand and thirdhand smoke, a humanistic approach using case-based discussions, hands-on training in pulse oximeter use, and the introduction of a household smoking exposure screening tool. Changes in cadres’ knowledge were evaluated using structured questionnaires administered before and after the intervention. Results: The average knowledge score increased from 65% at baseline to 86% after the intervention, representing an absolute increase of 21 percentage points and a relative improvement of 32.31%, exceeding the predefined success criterion of a ≥20% increase. Conclusion: The program was effective in enhancing Posyandu cadres’ understanding of smoking-related health risks and their ability to perform early hypoxia detection using pulse oximetry. Strengthening cadre capacity through integrated and practical training may support community-based pneumonia prevention and promote healthier, smoke-free environments for toddlers